PKM Pendidikan Melalui Kegiatan Keterampilan Motorik Siswa Paud Miftahul Ulum dan Al-Fadilah Desa Bulakan Kota Cilegon - Juhandi Juhandi; Nadiroh Nadiroh; Fatmawati Fatmawati; Setiawati Setiawati; Siti Hardianti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The motor nervous system is a series of nerves in the brain, spinal cord and muscle tissue that functions in human body movements such as speaking, walking and writing. One of them is in early childhood which helps improve their cognitive development. The aim of Community Service in the field of Education is to serve Bina Bangsa University students in implementing their knowledge in society. The stages carried out include conducting a survey, determining the use of motor methods, as well as service in PAUD in the Bulakan Village environment. The results of the service were carried out at two Early Childhood Education schools using different motor skill activity methods, both gross motor and fine motor. The conclusion of this PKM in the Education sector is good for finding out one of the education problems in one village regarding the education of early childhood students.